Phenotypic Characters Stability of Melodi Gama-3 Melon (Cucumis melo L.) Cultivar in Rainy Season Based on Multilocation Test - Budi Setiadi Daryono; Rizko Hadi; Yasir Sidiq; Sigit Dwi Maryanto (Institut Teknologi Sepuluh Nopember, 2014)
The study was conducted to determine the stability of MG3 cultivar characters in rainy season based on multilocation test. Used materials were MG3 melon cultivar originating from the Laboratory of Genetics, Faculty of Biology, UGM, and Action 434, Glamour Sakata, MAI, and LADIKA melon cultivars as commercial cultivars. Multilocation test was conducted in March – July 2013 (rainy season) in 3 provinces i.e., East Java, Daerah Istimewa Yogyakarta, and Central Java. Observation of phenotypic characters was conducted at the Laboratory of Genetics, Faculty of Biology, Universitas Gadjah Mada. Qualitative phenotypic characters data of cultivar MG3 and cultivars Action 434, Glamour Sakata, MAI, and LADIKA were compared qualitatively, while the quantitative characters data were analyzed by balanced ANOVA using PKBTSTAT 2.0 software. The results showed that fruit weight, fruit girth, skin thickness, and fruit vertical and horizontal diameter (longitudinal section) has a very significant difference by looking at the interaction of cultivar x locations, while flesh thickness has no significant difference. Qualitative characters were discussed according to its uniformity in three location. It was concluded that melon can also give yield in rainy season. MG3 was unstable for fruit weight and girth, skin thickness, and fruit vertical and horizontal diameter characters, while stable for flesh thickness character. MG3 having uniformity for fruit shape, unripe and ripe skin color, netting intensity, flesh color, flesh texture, and water content characters from three cultivating location, while for netting distribution, cavity shape, flesh flavor, and flesh aroma characters, it have not uniform yet.